Analisa Pengaruh Parameter 3D Printing dengan Metode Taguchi – Grey Relational Analysis Terhadap Kekasaran Permukaan dan Building Time Produk - Nurul Maulidah Al Awwaliyah; Bayu Wiro Karuniawan; Dhika Aditya Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
Additive Manufacturing Technology (AM) is interesting concern to be developed or usually called by 3D printing. In the production process, good quality output and optimal production are very important. Kind of dependent variable that affects product quality and high selling value is surface roughness, and that becomes the value of efficiency is the products build time. In this study, independent variable or parameters namely layer height; nozzle te mperature; and print speed are factors which is researched to obtain the optimal output. The design of experiment was made using the Taguchi method with orthogonal matrix of L9(34) by 3 times replication. Result analysis is using Grey Relational Analysis to obtain the optimal combination of parameters through the combined response. After conducting prediction experiments and getting optimal parameter predictions, a confirmation experiment is needed as a validation of the experiment's success. The optimal parameter results are the layer height of 0.05 mm, the nozzle temperature of 190oC, and the print speed of 60mm/s with average of roughness surface of 3.938?m and production time of ±109,933 minutes. Based on analysis, the contribution of layer height parameters were 41.2929%, the nozzletemperature 6.8134%, and the print speed 40.3769% throught the combined response.